The story of the Gadsbys - Kipling, Rudyard, 1865-1936 (Salt Lake City, UT : Project Gutenberg, 2001)
"The Story of the Gadsbys" by Rudyard Kipling is a work of fiction written during the late 19th century. The narrative revolves around Captain Gadsby, a British Army officer, and his interactions with various characters in colonial India, particularly focusing on his relationship with Minnie Threegan, who aspires to become his wife. The story captures themes of love, societal expectations, and the complexities of relationships in a unique setting. At the start of the narrative, we are introduced to characters in a Simla household, where Minnie and her friend Emma engage in lighthearted banter about Captain Gadsby, who visits their home frequently. Their conversation reveals Minnie's ambivalence towards Gadsby, whom she describes with a mix of admiration and disdain. We see her preparing for a meeting with him while grappling with her feelings. The scene also hints at social dynamics and romantic tensions, showcasing Kipling's signature blend of humor and keen observation as he sets the stage for what unfolds in their relationships. Overall, the opening portion establishes a vivid picture of life in colonial India, with its intricate social fabric and personal dramas. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Story_of_the_Gadsbys
Release date is 2001-09-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: India -- History -- British occupation, 1765-1947 -- Fiction; British -- India -- Fiction